2015
DOI: 10.1016/j.carbpol.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

The molecular origins of twist in cellulose I-beta

Abstract: The observation of twisted microfibrils in cellulose Iβ both in imaging and in molecular simulations has been reported and studied for years. This article reports a computational modeling study of cellulose Iβ twist showing its strong dependence on fibril diameter and no dependence on fibril length. We report that an important contribution to the twist in the model, empirically and analytically, is the hydrogen bonding that spans the glycosidic linkage, and that the characteristics of the chiral centers involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 45 publications
5
52
2
Order By: Relevance
“…covalent) and van der Waals terms. This observation is in agreement with previous simulation studies that have associated microfibril twist with changes in the intrachain, intra-layer, and inter-layer hydrogen bonding patterns (Paavilainen et al 2011;Bu et al 2015;Conley et al 2016;Kannam et al 2017).…”
Section: Twisting Dynamics and The Hierarchical Chiral Ordersupporting
confidence: 93%
See 2 more Smart Citations
“…covalent) and van der Waals terms. This observation is in agreement with previous simulation studies that have associated microfibril twist with changes in the intrachain, intra-layer, and inter-layer hydrogen bonding patterns (Paavilainen et al 2011;Bu et al 2015;Conley et al 2016;Kannam et al 2017).…”
Section: Twisting Dynamics and The Hierarchical Chiral Ordersupporting
confidence: 93%
“…All-atom MD simulations have been used to study the properties of cellulose in a broad context. This includes studies on the crystal structure of cellulose microfibrils (Matthews et al 2006;Wada et al 2011;Oehme et al 2015bOehme et al , 2018, and, as mentioned before, various aspects of the microfibril twist (Yui et al 2006;Matthews et al 2006;Yui and Hayashi 2007;Paavilainen et al 2011;Hadden et al 2013;Bu et al 2015;Conley et al 2016;Kannam et al 2017). Other studies have looked at the interactions of microfibrils with water (Yui et al 2006;Bergenstråhle et al 2008;Maurer et al 2013;Kulasinski et al 2015Kulasinski et al , 2017Lindh et al 2016;O'Neill et al 2017), their response to elevated temperatures (Matthews et al 2011(Matthews et al , 2012bZhang et al 2011); their mechanical properties (Paavilainen et al 2012;Saitoh et al 2013;Molnár et al 2018), aggregation and disintegration (Oehme et al 2015a;Paajanen et al 2016;Silveira et al 2016), chemical modification (Wada et al 2011;Paajanen et al 2016), enzymatic degradation (Beckham et al 2011;Orłowski et al 2015), and dissolution in ionic liquids (Gross et al 2011;Uto et al 2018); the pyrolytic degradation of cellulose (Zheng et al 2016;Paajanen and Vaari 2017); and radiation-induced defects…”
Section: Computationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the recent attention, twist is a much debated property of cellulose microfibrils with conjecture as to whether it exists and if so, what drives its formation [6,7,8]. In general, experiments performed on cellulose fibers of micrometer length and with a diameter of 20-50 nm have found that 180 • twist occurs over a length of a few hundred nanometers to a few micrometers [9,10,11,12].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The microfibrils can achieve width from 2-3 nm in the primary wall and 5-10 nm for secondary wall. The microfibrils may have some twisted regions (BU;CROWLEY, 2015;CONLEY et al, 2016). The amorphous regions occurs in a periodic distribution as show by ramie fibers studies (NISHIYAMA et al, 2003a).…”
Section: -Cellulosementioning
confidence: 99%